PROCESS MANAGEMENT–NEW WAY OF SELFGOVERNMENT FUNCTIONING - Štangová, Nora; Víghová, Agneša (European Scientific Journal, ESJ, 2015)
The article deals with processes, their identification and the key elements of process management, which enable the process approach in self-government. It also compares process and functional approaches from the viewpoint of management. We present a particular example of a municipal office, demonstrating individual types of processes, and continuing with their analysis and a proposal of process management implementation under particular conditions. Self-government represents an inseparable part of any societal system. It concerns each citizen by means of social, political, legislative and economic tools. Self-government in Slovakia is currently facing several key challenges, defined in most of concept documents dealing with the public administration reform. Constant pressure on the increase in effectiveness and professionalism also requires the application of new tools in the sphere of management. Process management is gradually finding its place in the public sector, even though it is originally an approach applied in entrepreneurial environment.The submitted article is dealing with this issue in broader contexts.